Modern façade technologies and media architecture - Shamaeva, Tatyana (project baikal, 2022)
Modern human is wrapped up in the virtual world of digital technologies. The lifestyle is changing and the requirements for the existing urban development are changing too. The architect has to look for new ways to create the appearance of modern architecture to attract attention to the surrounding reality. Innovative materials and digital technologies are actively used in architecture nowadays. Modern facade technologies are used for creating media architecture. By means of modern facade technologies new horizons in architecture are opening up, but the architect lacks sufficient experience in working with them. Professional duty forces us to master modern facade technologies in order to fully use them, anticipate dangerous points and be a participant in the ongoing changes in architectural design.
Keywords: modern facade technologies; media facade; media architecture; digital architecture